2004
DOI: 10.1007/s00268-004-7369-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Pylorus‐preserving Gastrectomy for Early Gastric Cancer: A Prospective Multicenter Trial

Abstract: The aim of the present study was to compare in a prospective, multicenter trial the results early and late after pylorus-preserving gastrectomy (PPG) versus conventional distal gastrectomy (CDG) with Billroth I anastomosis for early gastric cancer. Eighty-one patients with early gastric cancer were randomized and then underwent either PPG or CDG. Duration of operation, intraoperative blood loss, days until removal of the nasogastric tube, days until start of oral intake, and decrease in body weight were studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 19 publications
(26 reference statements)
2
48
2
1
Order By: Relevance
“…Our study showed that the incidences of early dumping syndrome and postoperative body weight loss were signifi cantly lower in the PPG than in the DGBI group. Contrary to previous studies, the incidence of gastric stasis with PPG was the same as that with DGBI [19]. In the longterm, it may be important to preserve the vagal nerve for improved gastric emptying.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Our study showed that the incidences of early dumping syndrome and postoperative body weight loss were signifi cantly lower in the PPG than in the DGBI group. Contrary to previous studies, the incidence of gastric stasis with PPG was the same as that with DGBI [19]. In the longterm, it may be important to preserve the vagal nerve for improved gastric emptying.…”
Section: Discussioncontrasting
confidence: 51%
“…Although several reports have evaluated outcomes following limited resection, the number of cases has been small, with too short an observation period to offer defi nitive evidence of the superiority of these procedures [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, T1N0 gastric cancer whose distal border is at least 4 cm proximal to the pylorus is a good indication for PPG [12]. This operation has an advantage over conventional distal gastrectomy, with a lower incidence of dumping syndrome, bile reflux gastritis, and nutritional deficit [13][14][15][16]. These advantages are attributable to preservation of the pyloric branch of the vagus nerve and the nutrient vessels supplying the antrum [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Dumping symptoms were reported in 4-46% of DG patients, but only in 0-13% of PPG patients [8][9][10]. Hotta et al [11] reported that nutritional status and serum albumin and hemoglobin levels were better in PPG than in DG patients.…”
Section: Discussionmentioning
confidence: 99%